Characterization and sequence diversity of the Gsp-1 gene in diploid species of the Aegilops genus. (May 2015) - Cuesta, Susana; Alvarez, Juan B.; Guzmán, Carlos
Abstract: Several studies have suggested a minor role in determining grain endosperm texture for the Gsp-1 gene, although appears related with the synthesis of the arabinogalactan-peptide. The current study evaluated the allelic variability of Gsp-1 genes in five diploid species of the Aegilops genus along with the molecular characterization of the main allelic variants found in each species and their phylogenetic relationships with the polyploid wheats. There was a high level of polymorphism in Gsp-1 genes – up to 19 alleles were obtained, of which 11 were novel. The processing of Gsp-1 amino acid sequences led to two main domains: AGP (arabinogalactan peptide) and GSP-1 (grain softness protein). Several substitutions were detected in both domains with respect to the bread wheat sequences, which could modify grain hardness. The sequences obtained showed relationship with the Gsp-B1 and Gsp-D1 genes of common wheat. These results showed that diploid Aegilops species are a rich resource of novel genetic variability for the Gsp-1 gene, whose hypothetical functionality should be tested in the genetic pool of modern wheat, valuing as the true role of these genes in grain hardness and their effective role as source of the AGP, a non-starch polysaccharide with health properties.